PEMBERDAYAAN TENAGA ADMINISTRASI SEKOLAH MENENGAH PERTAMA KOTA BATU: STUDI DESKRIPTIF - Imam Gunawan; Teguh Triwiyanto; Desi Eri Kusumaningrum; Muhammad Romady; Mutya Alfarina; Riski Ariska Widiana (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2018)
Abstract: Empowerment is the key to an organization’s increasing productivity and organizational performance. Schools as educational organizations have human resources (HR) that handle administrative services, which are commonly called School Administration Staff (SAS). The question posed in this research is how high is the level of empowerment of the SAS Junior High School Batu City? To answer the research question, this study uses a quantitative research approach. The research sample was SAS Junior High School Batu City with a total of 25 people. To measure indicators of level of empowerment of SAS by using a questionnaire developed by Kusumaningrum et al., (2017a). The research data were analyzed using descriptive statistics, namely by calculating the mean, standard deviation, and category description of each item. The results of the data analysis concluded that the empowerment level of the SAS Junior High School Batu City with the highest frequency of 9 people (36%) was in the good category and the average score was 70.2. Based on the description analysis category each item is known from 23 items, there are 7 items (30.43%) included in the low category, and 16 items (69.57%) are included in the high category. Keywords: empowerment, school administration staff Abstrak: Pemberdayaan merupakan kunci organisasi meningkatkan produktivitas dan kinerja organisasi. Sekolah sebagai organisasi pendidikan memiliki sumber daya manusia (SDM) yang menangani layanan administrasi, yang lazim disebut Tenaga Administrasi Sekolah (TAS). Pertanyaan yang diajukan dalam penelitian ini adalah seberapa tinggi tingkat pemberdayaan TAS SMP Kota Batu? Untuk menjawab pertanyaan penelitian tersebut, penelitian ini menggunakan pendekatan penelitian kuantitatif. Sampel penelitian adalah TAS SMP Kota Batu dengan jumlah 25 orang. Untuk mengukur indikator tingkat pemberdayaan TAS dengan menggunakan angket yang dikembangkan oleh Kusumaningrum dkk., (2017a). Data penelitian dianalisis menggunakan statistik deskriptif, yaitu dengan menghitung rerata, deviasi standar, dan deskripsi kategori setiap item. Hasil analisis data menyimpulkan bahwa tingkat pemberdayaan TAS SMP Kota Batu dengan frekuensi tertinggi 9 orang (36%) termasuk dalam kategori baik dan rerata skor sebesar 70,2. Berdasarkan analisis deskripsi kategori setiap item diketahui dari 23 item terdapat 7 item (30,43%) termasuk dalam kategori rendah, dan 16 item (69,57%) termasuk dalam kategori tinggi. Kata kunci: pemberdayaan, tenaga administrasi sekolah